Potensi Buah Delima Merah (Punica Granatum L.) Sebagai Pewarnaan Alternatif Pengganti Eosin pada Pewarnaan Papanicolaou - Rita Permatasari; Fuji Verdian Putra; Silvia Maharani (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Red Pomegranate (Punica granatum L.) belongs to the Punicaceae family which contains anthocyanins. The color of the pomegranate is caused by flavanoids, namely anthocyanins. Anthocyanins are pigments that can be used as natural dyes and can replace synthetic dyes. This study aims to measure the absorption optimization of red pomegranate (Punica granatum L.) on chicken oral epithelial smears as an alternative stain for eosin in Papanicolaou staining. This type of research is a laboratory study. This chicken mouth swab sample was carried out 7 treatments per five fields of view, with variations in concentration, namely, Pure/mother solution, dilutions of 1:1, 1:2, 1:3, 1:4, 1:5, and Papanicolauo's solution as a comparison. The results showed that dilutions of 1:3, 1:4, 1:5 with a mean rank value (14.00) obtained the lowest results, while the results that were closest to the reference solutions were dilutions of 1:1, 1:2 with a mean rank value ( 17.00) whereas the staining using the Papanicolaou solution/comparison obtained the mean rank value (33.00). The conclusion of the results of this study was that the staining of the preparations was stained but not the same as the control or significantly different 0.001 ≤ 0.016.